Remoção de BTEX em biorreatores anaeróbios sob condições metanogênicas, desnitrificantes e sulfetogênicas - Carneiro, Patrícia Marques (2012)
BTEX are monoaromatic hydrocarbons compounds which represent a high risk to the environment, mainly due to their toxic and carcinogenic characteristics. Among the methods usually applied to the removal of BTEX from contaminated waters, anaerobic treatment has drawn attention especially because of its low cost. Accordingly, anaerobic biodegradation of BTEX was assessed under methanogenic, denitrifying and sulfidogenic conditions. Additionally, an analytical method for detection of BTEX by gas chromatography using the technique of headspace was developed. Continuous-flow experiments were conducted using three anaerobic bioreactors in three subsequent complementary phases: 1) adaptation, with ethanol as the sole source of carbon and energy, 2) methanogenic, in presence of ethanol and BTEX, and 3) the same conditions as the previous phase but with two reactors supplemented with nitrate and sulfate acceptors, respectively, at a COD/acceptor ratio of approximately 11. Preliminarily, the specific methanogenic activity (SMA) of the microbial consortium was assessed using three different substrates (glucose, acetic acid and a mixture of volatile fatty acids), in which the volume of biogas produced and its composition in terms of methane and carbon dioxide were determined, respectively, by manometric method and gas chromatography. In the second phase of the continuous-flow experiment, the reactors were fed with a synthetic solution of BTEX (~ 5 mg/L of each compound) dissolved in ethanol and were operated at an HRT of 48 h at an average temperature of 27 °C. Concentrations of BTEX compounds were determined by the methodology developed and validated in this study, by which the BTEX were extracted by headspace (technique optimized by central composite rotational design) and analyzed by chromatography. The proposed analytical method for the determination of BTEX was very selective, precise, linear and presented low detection limit and quantification values, from 0.13 to 0.48 μg/L and from 0.43 to 1.61 μg/L, respectively. Glucose was the best substrate for the microbial consortium used, and a SMA value of 0.63 g COD/g SSV·d was obtained. The reactors evaluated were quite stable during all phases of the experiment with high COD removals (90% on average). Regarding BTEX removal, in general, the lowest removal efficiencies were found for benzene (40-63%), regardless of the final electron acceptor used, indicating that the biodegradation of this compound is difficult under anaerobic conditions, whereas the highest efficiencies were observed for xylenes, reaching a 90% removal. These numbers already took into account the possible interference of adsorption and volatilization. It was also noted that there should be a synergy between the different compounds and this may exert a strong effect on the BTEX removal efficiencies. Comparing the three reactors studied, it was not observed a significant improvement in the removal efficiencies of the compounds in the presence of nitrate or sulfate, but a tendency of an increase in efficiency between the reactors was verified as follows: methanogenic reactor > denitrifying reactor > sulfidogenic reactor. This performance can be attributed to the fact that the denitrifying and sulfidogenic microorganisms have preferred to oxidize ethanol instead of BTEX to reduce the acceptors, thus decreasing BTEX removal efficiencies under these conditions.